Combined liver and multivisceral resections: A comparative analysis of short and long‐term outcomes. Issue 7 (10th August 2020) - Júnior, Sérgio S.; Coelho, Fabricio F.; Tustumi, Francisco; Cassenote, Alex J. F.; Jeismann, Vagner B.; Fonseca, Gilton M.; Kruger, Jaime A. P.; Ernani, Lucas; Cecconello, Ivan; Herman, Paulo
Abstract: Background: En bloc liver and adjacent organs resections are technically demanding procedures. Few case series and nonmatched comparative studies reported the outcomes of multivisceral liver resections (MLRs). Objectives: To compare the short and long‐term outcomes of patients submitted MLRs with those submitted to isolated hepatectomies. Methods: From a prospective database, a case‐matched 1:2 study was performed comparing MLRs and isolated hepatectomy. Additionally, a risk analysis was performed to evaluate the association between MLRs and perioperative morbidity, mortality, and long‐term survival. Results: Fifty‐three MLRs were compared with 106 matched controls. Patients undergoing MLRs had longer operative time (430 [320‐525] vs 360 [270‐440] minutes, P  = .005); higher estimated blood loss (600 [400‐800] vs 400 [100‐600] mL; P  = .011); longer hospital stay (8 [6‐14] vs 7 [5‐9] days; P  = .003); and higher postoperative mortality (9.4% vs 1.9%, P  = .042). Number of resected organs was not an independent prognostic factor for perioperative major complications (odds ratio [OR], 1 organ = 1.8 [0.54‐6.05]; OR ≥ 2, organs = 4.0 [0.35‐13.84]) or perioperative mortality (OR, 1, organ = 5.2 [0.91‐29.51]; OR ≥ 2, organs = 6.5 [0.52‐79.60]). No differences in overall ( P  = .771) and disease‐free survival ( P  = .28) were observed. Conclusion: MLRs are feasible with acceptable morbidity but relatively high perioperative mortality. MLRs did not negatively affect long‐term outcomes.